DHRS9 Is a Stable Marker of Human Regulatory Macrophages. Issue 11 (November 2017) - Riquelme, Paloma; Amodio, Giada; Macedo, Camila; Moreau, Aurelie; Obermajer, Nataša; Brochhausen, Christoph; Ahrens, Norbert; Kekarainen, Tuija; Fändrich, Fred; Cuturi, Cristina; Gregori, Silvia; Metes, Diana; et al.
Abstract : Background: The human regulatory macrophage (Mreg) has emerged as a promising cell type for use as a cell-based adjunct immunosuppressive therapy in solid organ transplant recipients. In this brief report, dehydrogenase/reductase 9 (DHRS9) is identified as a robust marker of human Mregs. Methods: The cognate antigen of a mouse monoclonal antibody raised against human Mregs was identified as DHRS9 by immunoprecipitation and MALDI-MS sequencing. Expression of DHRS9 within a panel of monocyte-derived macrophages was investigated by quantitative PCR, immunoblotting and flow cytometry. Results: DHRS9 expression discriminated human Mregs from a panel of in vitro derived macrophages in other polarisation states. Likewise, DHRS9 expression distinguished Mregs from a variety of human monocyte-derived tolerogenic antigen-presenting cells in current development as cell-based immunotherapies, including Tol-DC, Rapa-DC, DC-10, and PGE2 -induced myeloid-derived suppressor cells. A subpopulation of DHRS9-expressing human splenic macrophages was identified by immunohistochemistry. Expression of DHRS9 was acquired gradually during in vitro development of human Mregs from CD14 + monocytes and was further enhanced by IFN-γ treatment on day 6 of culture. Stimulating Mregs with 100 ng/mL lipopolysaccharide for 24 hours did not extinguish DHRS9 expression. Dhrs9 was not an informative marker of mouse Mregs. Conclusion: DHRS9 is a specific and stable marker of human Mregs. Abstract : A brief definitive report that dehydrogenase/reductase 9 (DHRS9) is a robust marker of human, but not mouse, Mregs.